The waiting game: How securitization became the solution for the growth problem of the Eurozone. (April 2018) - Engelen, Ewald; Glasmacher, Anna
This paper takes a closer look at those parts of the European Commission's Capital Market Union (CMU) that bear upon the attempt to set up a new market for securitizations, called 'simple, transparent and standardized securitizations', in brief STS-securitization. The 'puzzle' at its heart is the discrepancy between narratives and content. While the narrative is about the construction of a US-style market-based financial system to overcome the problems of Europe's bank-based system and help medium-sized enterprises, the first legal initiative aims to create a European market for securitizations, which are a source of funding for large (mortgage) banks and as such are squarely at odds with the headline goals of the Capital Market Union. The paper discusses in detail key passages from the proposal to tease out the discrepancy between story and fact and ventures an explanation based on the identification of the interest coalitions behind the package.